2006
DOI: 10.1016/j.crvi.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A light- and electron-microscope study of hepatocytes of rats fed different diets

Abstract: Ketogenic diets are used in the treatment of epilepsy in children refractory to drug therapy. This study identifies changes in liver morphology in rats fed four different diets: a normal rodent chow diet, a calorie-restricted high-fat (ketogenic) diet and each diet supplemented with clofibric acid. Hepatocytes of rats fed the ketogenic diet show many lipid droplets and these are reduced to control levels when clofibrate is present in the diet. Mitochondria are enlarged in the livers of rats fed the ketogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The peroxisomal numbers in intestine did not change with clofibrate treatment, whereas, in other tissues like muscle, brain and heart, we could not observe any peroxisomes (data not shown). Previous studies in rats and mice fed clofibrate showed an increase in the number of mitochondria in the liver [69-71]. In this study, zebrafish fed ≥ 0.75% clofibrate showed an increase in the number of mitochondria only in heart cells (Figure 2B) compared to the control (Figure 2A).…”
Section: Resultssupporting
confidence: 63%
“…The peroxisomal numbers in intestine did not change with clofibrate treatment, whereas, in other tissues like muscle, brain and heart, we could not observe any peroxisomes (data not shown). Previous studies in rats and mice fed clofibrate showed an increase in the number of mitochondria in the liver [69-71]. In this study, zebrafish fed ≥ 0.75% clofibrate showed an increase in the number of mitochondria only in heart cells (Figure 2B) compared to the control (Figure 2A).…”
Section: Resultssupporting
confidence: 63%
“…Relative to the standard chow-fed mice, in the brains of the Western high fat diet-fed mice the mtDNA level was reduced by 37.5% and in the brains of the ketogenic diet-fed mice the mtDNA level was reduced by 50.8%. Since reduced mtDNA could indicate less mitochondrial mass, and ketogenic diets reportedly increase hippocampal, skeletal muscle, and liver mitochondrial mass (Eagles & Chapman 2007, Bough et al 2006, Ahola-Erkkila et al 2010, Noh et al 2004) we further assessed brain mitochondrial mass by measuring TOMM20, COX4I1, and COX2 protein levels. TOMM20, COX4I1, and COX2 protein levels were statistically comparable across the groups (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…The results in the liver are consistent with our previous observation that markers other than mitochondrial enzymes (e.g., cardiolipin) were not changed after one month of a KD [ 10 ]. Eagles et al showed that lipid droplets were increased in the liver of rats fed a KD [ 24 ]. However, these authors used a KD diet that was deficient in choline, which could lead to liver steatosis with a high-fat diet [ 25 ].…”
Section: Discussionmentioning
confidence: 99%